School principals’ views of teacher evaluation policy: lessons learned from two empirical studies - Flores, Maria Assunção (2017)
Teacher evaluation accountability policies are emerging world-wide. This paper examines principals’ perceptions of teacher evaluation in terms of commonalities and differences arising from two research projects conducted in Portugal and in the US. Perceptions of school principals in regard to a new policy on teacher evaluation as well as its perceived effects at school and conditions for its implementation will be analysed. Findings point to the challenges and successes of coping with mandated accountability measures in two different contexts. Principals balanced perceived conflicting goals, sought maintenance of positive teacher relationships and school culture, and managed the tensions of policy implementation and the making sense of its effects at school. Implications of the findings are discussed.